INOVASI FINANSIAL DALAM MENINGKATKAN EFISIENSI MANAJEMEN KEUANGAN PERUSAHAAN - Supatmin, Supatmin (Yayasan Education and Social Center, 2023)
This research aims to explore the impact of financial innovation on the efficiency of corporate financial management. The main focus of this research is to understand how the application of financial innovation can make a significant contribution to improving company performance and value in the long term. Qualitative research methods are used to explore the perceptions, experiences and views of financial managers, company leaders and other key stakeholders. Through in-depth interviews and content analysis, this research tries to answer key questions related to the implementation of financial innovation in the context of corporate financial management. The research results show that financial innovation substantially increases the efficiency of corporate financial management through the application of the latest technology, intelligent financial algorithms and innovative strategies. Significant benefits are found in cost management, tax planning, and investment decision making. Financial innovation also plays an important role in strengthening company relationships with stakeholders, creating transparency and increasing trust. Research emphasizes the importance of a deep understanding of innovative techniques and strategies in financial management, with the hope that managers and company leaders can utilize financial innovation to achieve financial goals, improve performance and company value. The conclusions of this research provide a basis for companies to continue to develop and adopt financial innovation as an integral part of their financial management strategy